Clinical outcome of proximal left anterior descending revascularization with everolimus eluting stents via transradial route: a single centre experience in Western Rajasthan, India - Mathur, Rohit; Kumar, Goutam; Gupta, Deepak; Sanghvi, Sanjeev; Baroopal, Anil (International Journal of Research in Medical Sciences, 2017)
Background: The proximal left anterior descending (LAD) artery stenosis represents the most important proximal site for obstructive coronary artery, as it supplies 40%–50% of the total left ventricular myocardium and could result in ischemia to a large area of myocardium. This study assesses the clinical outcome of patients with coronary artery diseases undergoing percutaneous revascularization with everolimus eluting stent implantation in the proximal left anterior descending coronary artery via trans radial route. Methods: 150 patients with significant angiographic lesion of proximal LAD artery stenosis treated with PTCA and stenting to proximal LAD via TRA were selected for study and were followed for one year. Results: Total 15 events were recorded 4 (2.6%) deaths and 11 (7%) MI and TLR was noted in 4% of patients. One (0.6%) case of acute stent thrombosis was recorded. Conclusions: Total MACE of this record (10% at 12 months of clinical follow-up) is consistent with those observed in the large randomized and multi-center studies with drug-eluting stents implanted in the proximal left anterior descending artery.